Experimental and Numerical Studies on Residual Stress in Wide Butt Welds - Yang Ding; Zhe Liu; Jia-Bao Yan; Liang Zong (Advances in Materials Science and Engineering)
The presence of residual stress in steel members can significantly compromise the stiffness and fatigue life of steel structural components. This influence becomes more serious for the wide butt welds in the construction of large-sized steel members due to the different residual stress distribution from the normal size butt welds. This paper experimentally studied the residual stress in the wide butt welds through an 8-experiment test program. High residual stress was produced during the wide butt welding and this stress was observed to be even higher than the yield strength of the steel. Moreover, this residual stress in the steel plate was firstly compressive and then transferred into tensile stress with the increase in the distance away from the butt weld line. The magnitude of the residual stress increased with the increase in the width of the welding seams. This paper also developed a finite element model by SYSWELD to simulate the residual stress produced by the wide butt welding. The accuracy of the FE simulation was checked by the reported test results. In order to reduce the residual stress, the ultrasonic peening method was adopted. The analysis results indicated that ultrasonic peening method effectively reduced the residual stress caused by the wide butt welding during the construction.